DAMPAK TINDAK PIDANA PENCUCIAN UANG TERHADAP SEKTOR EKONOMI DAN BISNIS - Adi Supriyo, Doni; Suwardi, Kaboel (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2020)
Money laundering as an international dimension of crime has a negative impact on a country's economy. This money laundering can not only be committed by individuals, but can also be committed by corporations. Money laundering is the process by which a person conceals the existence, illegal source, or illegal use of income, and then disguises the income to make it appear legitimate. This article will explain the impact of money laundering on the economic and business sectors.